Microbreweries and Culture in the Greater Madison Area - Ross, Eli; Sterling, Chandler; Daniels, Evan (My University, 2009)
In this study, we investigate how microbreweries serve a part of that neolocal ethic of the Madison area as they reflect and shape local meanings and attachments to place through experience and symbolism. People yearn for something in their community to attach themselves in order to foster a local identity. Microbreweries provide this attachment. As microbreweries rise in popularity, inhabitants can re-establish a connection with the communities they live as they have something to represent the new, unique, and the local. The Madison microbreweries and brewpub we studied are an integral part of the proliferation of community identity. They stay local and appeal to a specific customer base. The breweries themselves, events they host or sponsor, and the labeling and naming of their product are all characteristics of Madison microbreweries that reflect the culture of the Madison area. By examining several components of microbreweries in the greater Madison area, it became clear how these institutions contribute to community identity and the shape of Madison culture.
Includes figures, photographs and bibliography.
Keywords: Madison, WI; Microbreweries